Comparative Multi-Criteria Risk Analysis Applied to both Conventional and Green Technologies. (2017) - Bucovetchi, Olga; Stanciu, Radu D.; Pulfer, Roland
Abstract: Business Continuity (BC) is defined as the capability of the organization to continue delivery of products or services at acceptable predefined levels following a disruptive incident. The main objective of the paper is to identify the major threats to business continuity when switching the strategic spectrum from using conventional technologies to using green technologies. The authors used System of Systems Engineering (SoSE) methodology and Object-Oriented Programming (OOP) in order to compose a risk assessment model. In order to obtain a betted visualization of the result, within the research it was used TopEase as software environment. The main findings highlight that the risk spectrum is the same, yet the resilience map architecture does not seem similar, as the environmental conditions have greater impact to business continuity in case of green technologies compared to conventional ones.